2014
DOI: 10.1103/physrevd.90.103526
|View full text |Cite
|
Sign up to set email alerts
|

Astrophysical Bose-Einstein condensates and superradiance

Abstract: We investigate gravitational analogue models to describe slowly rotating objects (e.g., dark-matter halos, or boson stars) in terms of Bose-Einstein condensates, trapped in their own gravitational potentials. We begin with a modified Gross-Pitaevskii equation, and show that the resulting background equations of motion are stable, as long as the rotational component is treated as a small perturbation. The dynamics of the fluctuations of the velocity potential are effectively governed by the Klein-Gordon equatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…[26,27]. Finally, we would like to remark that, although we found that M M 0 for very large compactness, and one could thus infer that matter become almost irrelevant inside a black hole [10], the above picture inherently requires the presence of matter, whose role in black hole physics we believe needs more investigations [22][23][24][25].…”
Section: Conclusion and (Quantum) Outlookmentioning
confidence: 84%
“…[26,27]. Finally, we would like to remark that, although we found that M M 0 for very large compactness, and one could thus infer that matter become almost irrelevant inside a black hole [10], the above picture inherently requires the presence of matter, whose role in black hole physics we believe needs more investigations [22][23][24][25].…”
Section: Conclusion and (Quantum) Outlookmentioning
confidence: 84%
“…where the normalisation N H = √ 3/ π 2 − 6 ζ(3) 1.06, we introduced the dimensionless variables 5) and the states |E i = m 1/2 |ω i , such that the identity in the continuum can be written as…”
Section: Bec With Thermal Quantum Hairmentioning
confidence: 99%
“…Since the source represented by such quantum states is by construction (mostly) localised within R H , this shows that r = r H is a horizon for the system. Given the spectral coefficients (3.20), the corresponding horizon wave-function reads 5) where the state |R H represents the discrete part of the spectrum and is defined so that 6) and the states…”
Section: Horizon Wave-function and Backreactionmentioning
confidence: 99%
“…The quantum fluctuations approximately follow a Gaussian distribution centered around zero. The depletion process is given by a Poisson distribution [18][19][20][21].…”
Section: Competing Fluctuationsmentioning
confidence: 99%
“…In fact, some phenomena, like Hawking radiation, the Bekenstein entropy, or, the information paradox, can only be fully understood in this quantum picture [9][10][11][12][13][14][15] (cf. also [16][17][18][19][20][21][22][23][24][25][26][27] for recent progress).…”
Section: Introductionmentioning
confidence: 99%